Pain processing in the human brainstem and spinal cord before, during, and after the application of noxious heat stimuli. Issue 10 (October 2018) - Stroman, Patrick W.; Ioachim, Gabriela; Powers, Jocelyn M.; Staud, Roland; Pukall, Caroline
Abstract : Abstract: Descending regulation of spinal cord responses to nociceptive signaling has a strong influence on pain perception. Previous studies using functional magnetic resonance imaging (fMRI) have indicated that in addition to reactive responses to nociceptive signals, there is a continuous component to regulation, and that it may vary with differences in pain sensitivity. We hypothesize that this continuous regulation component occurs routinely in fMRI studies before noxious stimulation, as well as during, and after stimulation. This hypothesis was tested by analyzing data from 59 healthy participants in 4 previous fMRI studies in our laboratory using noxious heat stimuli. Analyses included structural equation modeling to identify coordinated blood oxygenation-level–dependent (BOLD) signal variations between regions (ie, connectivity) and Bayesian regression of BOLD time-series responses in relation to pain ratings and stimulus temperatures. The results demonstrate the periaqueductal gray–rostral ventromedial medulla–spinal cord descending modulation pathway, influenced by input from the hypothalamus, parabrachial nucleus, and nucleus tractus solitarius. Connectivity between specific regions is observed to vary in relation to pain sensitivity. The results support the conclusion that homeostatic autonomic control influences the net descending pain regulation, and therefore influences pain sensitivity. The results describe the overall properties of pain processing (specifically pain elicited by heat) in the healthy human brainstem and spinal cord, and mechanisms for variation across individuals. This understanding is expected to be important for studies of how pain processing is altered in chronic pain conditions. Abstract : Supplemental Digital Content is Available in the Text.Functional magnetic resonance imaging of the brainstem and spinal cord in 59 healthy participants indicates that autonomic regulation influences descending pain regulation and individual pain sensitivity.